Cultural Documentation of Statue Art Collections in Bandung's Nuart Sculpture Park - Prastiyo, Tongat Eko; Khadijah, Ute Lies Siti; Perdana, Fitri (Universitas Pendidikan Indonesia, 2022)
This research is about cultural documentation of sculptures in Nuart Sculpture Park Bandung. The main focus of this research is to identify and documenting the sculptures art in Nuart Sculpture Park. The research method is a qualitative research with an action research approach, this approach seeks to provide improvements or changes through the action-reflection process so that the process can occur repeatedly. This study uses a spiral model from Kemmis and Taggart, this research method consists of four stages, namely planning, acting, observing and reflecting. At the planning stage, it is done by collecting and identifying information through observation, interviews and literature study. The acting stage is the stage of making booklet based on the information that has been obtained. The observing stage is the stage of observing the effectiveness of the acting stage that has been carried out. The last stage is the reflecting stage, which is analyzing the results of the observing stage to determine whether or not it is necessary to repeat the research cycle. The object of this research is sculptures in Nuart Sculpture Park and the research’s subjects are 4 sources and using purposive sampling technique. The result of this study is a booklet that has been tested publicly by Nuart Sculpture Park visitors and Nuart Sculpture Park administrative employees with positive results so that the booklet can be used.